Interactive Mobile Technologies for Consumer Behavior Management: Insights from Digital Marketing Applications - Luo Hao; Sobia Irum; Nazarenko Inna; Nohman Khan, (International Journal of Interactive Mobile Technologies (iJIM), 2025)
The rapid proliferation of mobile technologies has transformed digital marketing, yet fragmented evidence limits understanding of how interactive mobile tools shape consumer behavior. Existing studies often isolate technologies such as push notifications, geo-fencing, chatbots, and AR/VR without addressing their synergistic effects, leaving a theoretical and practical gap in consumer behavior management. This study aimed to systematically examine how interactive mobile technologies influence consumer engagement, decision-making, and brand loyalty, while developing an integrative framework to guide mobile-first marketing strategies. A systematic literature review was conducted following PRISMA guidelines, drawing on 125 peer-reviewed articles published between 2015 and 2025. Structural topic modeling (STM) was employed to identify thematic patterns and trace the evolution of research trends across journals and time periods. The analysis revealed five dominant themes: 1) AR/VR and immersive mobile technologies, 2) chatbots and AI interactions, 3) gamification and interactive engagement, 4) consumer behavior and decision-making, and 5) brand loyalty and customer engagement. Findings show that mobile-specific features—personalization, adaptability, and real-time measurement—act as powerful behavioral drivers, enabling tailored interventions and sustained consumer relationships. However, challenges emerged around privacy, consumer fatigue, and ethical use of behavioral data. This study contributes by consolidating fragmented research into a structured framework that explains how mobile technologies operate as behavioral intervention systems. The results provide theoretical insights into mobile consumer behavior models and practical guidance for marketers deploying mobile-first strategies. Future research should extend toward longitudinal, cross-cultural, and hybrid-technology designs to capture sustained and synergistic effects.